Molecular determinant deciphering of MIC-guided RND efflux substrates in E. coli - Revol-Tissot, Johan; Boyer, Gérard; Alibert, Sandrine (Frontiers in Drug Discovery, 2024)
Antimicrobial resistance poses an urgent and formidable global public health threat. The escalation of bacterial multidrug resistance to antibiotics has the potential to become a leading cause of global mortality if there is no substantial improvement in antimicrobial development and therapy protocols. In light of this, it is imperative to identify the molecular determinants responsible for the reduced antibiotic activity associated with RND efflux pumps. This comprehensive study meticulously examines Minimum Inhibitory Concentration (MIC) data obtained from in vitro tests for various antibiotic families and non-active dye compounds, sourced from diverse literature references. The primary focus of this study is to assess the susceptibility of these agents to efflux-resistant Escherichia coli strains, integrating both MIC data and relevant physicochemical properties. The central objective is to unveil the specific substituents that significantly influence the uptake process mediated by the AcrAB-TolC efflux system. This exploration seeks to reveal the consequences of these substituents on pharmacodynamic responses, providing valuable insights into Structure-Activity Relationships. It is noteworthy that this analysis represents a pioneering effort, with prospective implications for RND efflux pump-producing strains. Ultimately, deciphering efflux markers is crucial to effectively mitigate the emergence of specific resistance and to better monitor the role of this primary resistance mechanism in Gram-negative bacteria, particularly as observed in clinical antibiotic therapy practice.